Investigation of the guiding effect of watershed compensation policy on green credit issuance: evidence from environmental law enforcement - Zhang, Xiuqin; Zhou, Siyu (Elsevier, 2026)
With the continuous deepening of green finance and ecological protection concepts, researching the institutional driving mechanisms behind green credit issuance has become increasingly important. This paper explores the relationships and heterogeneity among watershed compensation policy, environmental law enforcement intensity, and green credit issuance. The study finds a positive correlation between watershed compensation policy and green credit issuance. Moderating effect analysis indicates that environmental law enforcement intensity plays a regulatory role in the relationship between watershed compensation policy and green credit issuance. Heterogeneity analysis reveals that the promotional effect of watershed compensation policy on green credit issuance varies between regions with high and low environmental regulatory intensity. Furthermore, the regulatory role of environmental law enforcement intensity in the relationship between watershed compensation policy and green credit issuance also exhibits heterogeneity between regions of high and low ecological environmental quality. This research provides theoretical basis and empirical support for improving green finance policy design and enhancing ecological environmental governance.